x⁴=(3x-10)²
x⁴=9x²-60x+100
x⁴-9x²+60x-100=0
x₁=2
x⁴-9x²+60x-100 I_x-2
x⁴-2x³ I x³+2x²-5x+50
2x³-9x²
2x³-4x²
-5x²+60x
-5x²+10x
50x-100
50x-100
0
x³+2x²-5x+50=0
x₂=-5
x³+2x²-5x+50 I_ x+5
x³+5x² I x²-3x+10
-3x²-5x
-3x²-15x
10x+50
10x+50
0
x²-3x+10=0 D=-31 ⇒
Уравнение действительных корней не имеет.
ответ: х₁=2 х₂=-5.
Объяснение:
Удачи!!!
1.
216х² - 6у⁴ = 6 * (36х² - у⁴) = 6*(6х - у²)(6х + у²) (ответ Е),
2.
а)
S = 6а² = 6*(3х - 4)² = 6*(9х² - 24х + 16) = 54х² - 144х + 96,
б)
V = а³ = (3х - 4)³ = 27х³ - 108х² + 144х - 16,
3.
а)
4,3² - 2,58 + 0,3² = 4,3² - 2*4,3*0,3 + 0,3² = (4,3 - 0,3)² = 4² = 16,
б)
(44² - 12²) / (56² - 16²) = (44 - 12)(44 + 12) / (56 - 16)(56 + 16) =
= (32*56) / (40*72) = 28/45,
4.
1 число - х,
2 число - (х-52),
х² - (х-52)² = 208,
х² - х² + 104х - 2704 = 208,
104х = 208 + 2704,
104х = 2912,
х = 28 - 1 число,
х-52 = 28 - 52 = -24 - 2 число
2Y - X = - 7
X = 2Y + 7
X^2 = (2Y+7)^2 = 4Y^2 + 28Y + 49
X^2 - Y^2 = 24
4Y^2 + 28Y + 49 - Y^2 = 24
3Y^2 + 28Y + 25 = 0
D = 784 - 12*25 = 784 - 300 = 484
V D = 22
Y1 = - 28 + 22 \ 6 = - 6\6 = - 1
Y2 = - 50\6 = - 25\3 = - 8 1\3
X = 2y + 7
X1 = - 2 + 7 = 5
X2 = - 50\3 + 21\3 = - 29\3 = - 9 2\3